1998
DOI: 10.1046/j.1365-2761.1998.00085.x
|View full text |Cite
|
Sign up to set email alerts
|

Aeromonas hydrophila causes ‘black disease' in fairy shrimps (Anostraca; Crustacea)

Abstract: A total of 51 bacterial strains were isolated from fairy shrimps [Branchipus schaefferi (Fisher), Chirocephalus diaphanus (Prévost) and Streptocephalus torvicornis (Waga)] showing signs of 'black disease'. The fairy shrimps showed black nodules on the thoracic appendages, the cercopods, the antennae and sometimes at the back of the head. The infection sites on the thoracic appendages were restricted to the proximal parts of the endopodite, the exopodite and endite I. In order to check Koch's postulates, pure b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 8 publications
3
9
0
Order By: Relevance
“…black disease, is a major factor limiting their cultivation. The appearance of the disease found on fairy shrimp in Thailand is similar to that found in other countries including Spain, Algeria, Germany, America, Belgium (Dierckens, Vandenberghe, Beladjal, Huys, Mertens & Swings 1998) and Japan (Nambu, Tanaka & Nambu 2007). The disease is considered to be a cause of mortality in fairy shrimp and also has an adverse effect on commercial cultivation.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…black disease, is a major factor limiting their cultivation. The appearance of the disease found on fairy shrimp in Thailand is similar to that found in other countries including Spain, Algeria, Germany, America, Belgium (Dierckens, Vandenberghe, Beladjal, Huys, Mertens & Swings 1998) and Japan (Nambu, Tanaka & Nambu 2007). The disease is considered to be a cause of mortality in fairy shrimp and also has an adverse effect on commercial cultivation.…”
Section: Introductionsupporting
confidence: 80%
“…were used as food. The fairy shrimp were then exposed to bacterial strains for 5 days (Dierckens et al. 1998) and their behaviour was observed daily.…”
Section: Methodsmentioning
confidence: 99%
“…Also in various animal species, Aeromonas has been associated with a range of infections. Most notably, such cases have been frequently reported in poikilothermic animals including amphibians, reptiles, fish, and shrimps (Marcus 1971(Marcus , 1981Shotts et al 1972;Brackee et al 1992;Burns et al 1996;Gosling 1996;Schilliger 1997;Dierckens et al 1998). One of the first animal infections attributed to Aeromonas was the so-called redleg disease in frogs (Sanarelli 1891).…”
Section: Pathogenicity Clinical Relevancementioning
confidence: 99%
“…A recent study showed that black disease, caused by Aeromonas spp., leads to mortality in fairy shrimp. The disease is recognized as having a severe effect on productivity (Dierckens, Vandenberghe, Beladjal, Huys, Mertens & Swings 1998;Saejung, Hatai, Wada, Kurata & Sanoamuang 2011). To overcome black disease, several organic salts, chemical disinfectants and antibiotics were tested to determined levels of pathogen inhibition in vitro.…”
Section: Introductionmentioning
confidence: 99%